Sex Differences in Neurophysiological Changes Following Voluntary Exercise in Adolescent Rats - Ferguson, Lindsay; Giza, Christopher C.; Serpa, Rebecka O.; Greco, Tiffany; Robert, Hannah; Folkerts, Michael; Prins, Mayumi L. (Frontiers in Neurology, 2021)
BACKGROUND: Adolescence is a period of time characterized by the onset of puberty and is marked by cognitive and social developments and gross physical changes that can play a role in athletic performance. Sex differences are present with differences in body size, height, physiology and behavior which contribute to differences in athletic performance as well. Pre-clinical studies representing this active group are lacking. METHODS: Acute and chronic effects of exercise were evaluated. Male and female adolescent rats were given voluntary access to a running wheel for 10 consecutive days. Running behavior (males and females) and estrous cycling (females only) were analyzed daily. A second group was given 10 days of voluntary access to a running wheel, then rested for 10 days to determine the long-term effects of exercise on the adolescent brain. Brain and muscle tissue were harvested at 10 and 20 day time points to understand exercise-dependent changes in mitochondrial activity and neuroplasticity. Animal cohorts were carried out at 2 different sites: University of California Los Angeles and Pepperdine University. RESULTS: On average, running distance, intensity of run, and length of running bout increased for both males and female rats across the 10 days measured. Females ran significantly further and at longer intervals compared to males. Cortical and muscle expression of PGC1α showed similar levels at 10 days regardless of sex and exercise. There was a significant increase in expression at 20 days in all groups correlating with body size (p’s<0.05). Cortical and hippocampal levels of BDNF were similar across all groups, however, BDNF was significantly higher in exercised females at the acute compared to long-term time point. DISCUSSION: Adolescent rats allowed 10 days of exercise show changes in physiologic function. There are sex differences in running behavior not impacted by sex hormones. These results are important to further our understanding of how exercise impacts the adolescent brain.